The Physical Exercise Program during Post-Surgery Rehabilitation of Elderly Patients Diagnosed with Thrombophlebitis of the Lower Limbs in Jordanian Hospitals - Mutasem Abdel Wahhab Khalaf Al-Soub (Journal of Global Pharma Technology, 2018)
Deep vein thrombosis (DVT) or thrombophlebitis is frequently found in human limb veins and it is is a manifestation of venous thromboembolism (VTE). Thrombosis is a process of intravital blood clot formation inside blood vessels. This may be lethal. The mortality rate associated with this disease is higher than that of many extremely dangerous disorders. In most countries, statistical figures provided by healthcare systems regarding thrombosis patients are high. Aim of the study is checking the physical exercise program efficiency designed for post-surgery rehabilitation of elderly patients diagnosed with lower-limb thrombophlebitis in Jordanian hospitals. Research methodology was based on theoretical analysis and scientific and methodical literature, pedagogical observation, medical and biological research methods, as well as on statistical methods. The studied group was formed by elderly patients diagnosed with lower-limb thrombophlebitis. They underwent surgery and were sent to restore with a one-year (2014-2015) rehabilitation program in the Physiotherapy Department of the AL-Karak State Hospital (Jordan). The patients were in the age of 55-60 years. Before doing exercises, patients have not been feeling pain or distress. The rehabilitation program was applied for 30 minutes three times per week. Each session was attended by four patients. Results were processed by means of mathematical statistics and by calculating significant differences with the Student’s t-test. We have substantiated the use of a physical exercise program designed for post-surgery rehabilitation of elderly patients with thrombophlebitis of the lower limbs. This paper provides a research on bodily exercise program efficiency during one-year rehabilitation period of elderly patients, who underwent surgical management of lower-limb thrombophlebitis. The program has improved a number of patient characteristics: body weight, blood pressure, heart rate, physical condition index, the adaptive capacity of cardiovascular system.Keywords: Diagnosis, Thrombophlebitis, Physical Rehabilitation, Exercise, Elderly Patients.